Residents perception of environmental features and theft in Calabar south local government area of Cross River State, Nigeria - AYUK , Awunghe Achu; NEJI, Obi Ndifon; OWAN, Emeka J.; UNDIYAUNDEYE, Florence A.; ANOKAM, Eugenia O; EKPOUDO, Anthony; IWARA, Iwara Eno; ETENG, Felix Onen; ISOKON, Brown; TIKU, Oru Takim; UCHEGBUE, Henrietta Osayi; ABUL, Uyang Francis; et al. (Journal of Ecohumanism, 2024)
This research aims to explore the perceptions of residents regarding environmental factors and theft in Calabar South Local Government Area of Cross River State, Nigeria. To achieve the purpose of the study two hypotheses was formulated. Relevant literature was reviewed and two theories employed to explain the phenomenon under study. Pearson Product Moment Correlation Analysis statistical tool was utilized to test the hypotheses. The results revealed that, a significant relationship exist between the aforementioned environmental features and theft. Based on the findings, the study recommended among other things to include: the need for homeowners to block unnecessary access points within their premises that are used by pedestrians to reach other streets or houses; government should facilitate the provision of affordable housing in the area to alleviate congestion resulting from the limited availability of buildings, which underscores the significance of addressing crowded and permeable premises as crucial contributors to theft- whence possible to mitigate the prevalence of theft and enhance the safety and well-being of residents in the area.